A robust hydrogen evolution catalyst based on crystalline nickel phosphide nanoflakes on three-dimensional graphene/nickel foam: high performance for electrocatalytic hydrogen production from pH 0–14. Issue 5 (9th January 2015) - Han, Ali; Jin, Song; Chen, Huanlin; Ji, Hengxing; Sun, Zijun; Du, Pingwu
Abstract : A highly efficient cathode containing 3D Ni2 P/graphene layers/nickel foam has been successfully constructed for electrocatalytic H2 evolution reaction (HER). Abstract : The design and preparation of highly active catalysts for the hydrogen evolution reaction (HER) is very important for water splitting. Herein, we report a highly active HER catalyst, which is synthesized by loading nanostructured nickel phosphide (Ni2 P) on three-dimensional few-layer graphene/nickel foam (G@NF). G@NF was successfully prepared by a chemical vapor deposition process in the presence of methane at high temperature. Compared with nickel phosphide, G@NF, as well as commercial platinum, the Ni2 P–G@NF catalyst exhibited very high activity in electrocatalytic H2 production from water (∼7 mV overpotential in alkaline solutions, pH ∼ 14; and ∼30 mV overpotential in acidic solutions, pH ∼ 0). The high catalytic activity of Ni2 P–G@NF is attributed to the excellent performance of Ni2 P, the large 3D framework which facilitates proton accessibility and electron transfer, and the high surface area.